Penerapan Manajemen Sumber Daya Manusia Strategik Melalui Pelatihan SDM : Studi Pada Universitas Katolik Widya Karya - Andy Endra Krisna (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
The development of Human Resources (HR) is needed by companies or organizations. The function of this development is to improve human resources to become more productive. Therefore, strategic human resource management is needed to be applied. With productive human resources owned by a company, the company will be more effective in achieving the goals that the company will achieve. Strategic HR development can be done through trainings. These trainings are usually based on company’s needs or employee’s needs. Widya Karya Catholic University of Malang (UKWK) is a private higher education institution in the city of Malang. Nowadays, there are more and more demands for the development of institutions, especially those who operate in the field of higher education, such as UKWK Malang. To meet the demands of these developments, this campus must hold training after training for its human resources. The research method used in this research is a descriptive method with a qualitative approach. The results of this research are described descriptively.